Desenvolvimento e validação de conteúdo da escala de literacia em atividade física para adolescentes - Almeida, Josélia dos Santos. (2024)
The aim of this study was to develop and determine the content validity of the physical activity literacy scale for adolescents. This is a methodological study with the following steps: Construction of the scale's theoretical framework; Development of the scale; Content validity. To construct the scale, a literature search was carried out to identify studies, concepts and scales of physical activity literacy. The first version of the scale consisted of 35 items, distributed in four dimensions: knowing/understanding (11 items), knowing where to look (11 items), knowing how (6 items), and knowing how to evaluate (7 items). In each dimension, the items were anchored with 5 Likert-type response options (“I know nothing”, “I know a little”, “I know well”, and “I know very well”). Content validity was performed by 13 experts who evaluated the clarity of language; theoretical relevance; and practical relevance. To analyze the results, the content validity index of each item (IVCi) and the total content validity index for each dimension and for the scale in general (IVCt) were calculated. The ICVi was calculated based on the scores given by the experts to each item with the highest possible scores (3 and 4). Items that received scores (1 and 2) were reviewed and/or excluded from the scale. The results of the content analysis of the items demonstrated adequate values for clarity of language, theoretical relevance, and practical relevance (≥0.70). The CVIt of the dimensions know/know and know where to look (≥0.90) was considered adequate, while the dimensions know how (≤0.49) and know how to evaluate (≤0.59) were considered below expectations. The CVIt for the four dimensions of the scale was considered acceptable (≥0.70). The final version of the scale had 23 items, distributed across three dimensions: know/know (11), know where to look (8), and know how to evaluate (4). It was concluded that the scale presented satisfactory levels of content validity. Future studies should continue to perform reliability analysis (reproducibility, internal consistency) and construct validity of the physical activity literacy scale for adolescents.